Night flight to Paris - Black, Cara, 1951- (Black, Cara, 1951- Kate Rees WWII novel, 2023)
"October 1942: it's been two years since Kate Rees was sent to Paris on a British Secret Service mission to assassinate Hitler. Since then, she has left spycraft behind to take a training job as a sharpshooting instructor in the Scottish Highlands. But her quiet life is violently disrupted when Colonel Stepney, her former handler, drags her back into the fray for a dangerous three-pronged mission in Paris. Each task is more dangerous than the next: Deliver a package of penicillin to sick children. Assassinate a high-ranking German operative whose knowledge of secret invasion plans could turn the tide of the war against the Allies. Rescue a British agent who once saved Kate's life, and get out. Kate will encounter sheiks and spies, poets and partisans, as she races to keep up with the constantly shifting nature of her assignment, showing every ounce of her Oregonian grit in the process. New York Times bestselling author Cara Black has crafted another heart-stopping thrill ride that reveals a portrait of Paris at the height of the Nazi occupation"--